The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.19173/irrodl.v17i5.2541
|View full text |Cite
|
Sign up to set email alerts
|

Development of Open Textbooks Learning Analytics System

Abstract: Textbook costs have skyrocketed in recent years, putting them beyond the reach of many students, but Learning analytics offers a faster and more objective means of data collection and processing than traditional counterparts, such as surveys and questionnaires, and-most importantly-with their capability to provide direct evidence of learning, they present the opportunity to enhance both learner performance and environment. With such benefits on offer, it is hardly surprising that the optimism surrounding learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Track individual learners' online and offline interactions with open learning resources Prasad et al (2016) 43. University of Wollongong Analysis, intervention, reflection Visualize patterns of student interactions on discussion forums Allow instructors to identify at-risk students and potentially high and low performing students for planning interventions, and the extent to which a learner community is developing in a class Mat et al (2013) Table AI.…”
Section: Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Track individual learners' online and offline interactions with open learning resources Prasad et al (2016) 43. University of Wollongong Analysis, intervention, reflection Visualize patterns of student interactions on discussion forums Allow instructors to identify at-risk students and potentially high and low performing students for planning interventions, and the extent to which a learner community is developing in a class Mat et al (2013) Table AI.…”
Section: Monitoringmentioning
confidence: 99%
“…open source resources could be modified and adapted by anyone to meet specific user needsPrasad et al (2016) University of Sydney LA features such as instant feedback and auto-grading are especially useful for instructors teaching subjects in computer science educationGramoli et al (2016) …”
mentioning
confidence: 99%
“…Another approach to providing value with relatively low effort is instrumenting already existing resources, as Prasad et al (2016) have shown by developing an epub (an electronic book format) viewer to monitor interactions similarly to how a MOOC does; many courses in schools use books that are available as PDFs, therefore instrumenting such books may provide clickstream-like information on reading habits without the requirement to redevelop course resources. In addition, for those subjects that perform field studies, techniques from mobile learning may be adapted, with success shown if the developed applications actually support the student in their learning goals required by the existing course content while providing LA data (Fulantelli et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lockyer, Heathcote, and Dawson (2013) analyze how analytics can facilitate pedagogical actions for learning designs. Another study highlights that LA may provide insights on how to assess students based on the OERs’ impact (Prasad, Totaram, & Usagawa, 2016). However, Persico and Pozzi (2015) argue that most of the research in learning analytics has concentrated attention to the contribution of learning analytics during the enactment of learning experiences and not in a design phase.…”
Section: Theoretical Background and Related Workmentioning
confidence: 99%